EFFICIENCY OF QR CODE IMPLEMENTATION IN RELATION TO SKILLS ALIGNMENT IN SELECTED INDONESIAN ENTERPRISES TOWARD A PROPOSED BUSINESS DEVELOPMENT PLAN AND MODEL - Magbato Ebora, Angelito; Oliver F. Cortez, Richard; A. Sario, Jay (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
QR codes, with their multidimensional data storage and widespread mobile usage, have become crucial in modern commerce, streamlining transactions and improving user experiences. Despite their benefits, challenges like data security threats persist, necessitating a balanced approach. The study aims to explore QR code implementation efficiency, particularly in skills training, within Indonesian enterprises, addressing a literature gap on this specific context and QR code integration into training. The study's primary objectives include investigating the adoption and impact of QR code technology within select Indonesian companies. It seeks to understand participants' demographic profiles, assess QR code implementation efficiency across various operational aspects, explore demographic differences in perceived efficiency, evaluate the alignment of skills training with QR code utilization, and establish any significant relationship between QR code implementation efficiency and skills training alignment among participants. The study sought standardized information on QR code adoption, utilizing surveys for varied perspectives. The study finds that Indonesian employees are mainly young, with 70.3% under 30, indicating potential openness to QR code technology. Despite a balanced gender distribution, mostly non- managerial roles are held by respondents (76.6%). Efficiency ratings across sectors (composite means: 3.89 to 4.16) highlight QR codes' effectiveness. Demographics like age, gender, and education don't significantly affect QR code perceptions. While QR-related skills training alignment is generally rated adequately (composite mean: 3.62), variability suggests areas for improvement. The study highlights a youthful demographic among Indonesian employees, indicating potential openness to QR code technology adoption. Despite balanced gender distribution, non-managerial roles are predominant. Efficiency ratings across operational sectors show QR codes' perceived effectiveness in boosting productivity. Demographic factors like age, gender, and education don't significantly affect perceptions of QR code efficiency, suggesting widespread acceptance. However, while QR-related skills training alignment is generally rated adequate, variability suggests room for improvement in ensuring effective skill development for optimal QR code utilization.